Cardiac Fibroblast-Derived Extracellular Matrix (Biomatrix) as a Model for the Studies of Cardiac Primitive Cell Biological Properties in Normal and Pathological Adult Human Heart. (2nd May 2013) - Castaldo, Clotilde; Di Meglio, Franca; Miraglia, Rita; Sacco, Anna Maria; Romano, Veronica; Bancone, Ciro; Della Corte, Alessandro; Montagnani, Stefania; Nurzynska, Daria
Abstract : Cardiac tissue regeneration is guided by stem cells and their microenvironment. It has been recently described that both cardiac stem/primitive cells and extracellular matrix (ECM) change in pathological conditions. This study describes the method for the production of ECM typical of adult human heart in the normal and pathological conditions (ischemic heart disease) and highlights the potential use of cardiac fibroblast-derived ECM for in vitro studies of the interactions between ECM components and cardiac primitive cells responsible for tissue regeneration. Fibroblasts isolated from adult human normal and pathological heart with ischemic cardiomyopathy were cultured to obtain extracellular matrix (biomatrix), composed of typical extracellular matrix proteins, such as collagen and fibronectin, and matricellular proteins, laminin, and tenascin. After decellularization, this substrate was used to assess biological properties of cardiac primitive cells: proliferation and migration were stimulated by biomatrix from normal heart, while both types of biomatrix protected cardiac primitive cells from apoptosis. Our model can be used for studies of cell-matrix interactions and help to determine the biochemical cues that regulate cardiac primitive cell biological properties and guide cardiac tissue regeneration.